2002
DOI: 10.1073/pnas.022608799
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 is a major stress-regulated gene: Implications for stress-induced thrombosis in aged individuals

Abstract: Plasminogen activator inhibitor-1 (PAI-1) is one of the primary inhibitors of the fibrinolytic system and has been implicated in a variety of thrombotic disorders. In this report, stress-induced changes in murine PAI-1 gene expression were investigated to study the role of this inhibitor in the development of stress-induced hypercoagulability. Restraint stress led to a dramatic induction of plasma PAI-1 antigen and of tissue PAI-1 mRNA with maximum induction in adipose tissues. In situ hybridization analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
132
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 51 publications
4
132
0
1
Order By: Relevance
“…[25][26][27][28] First, in spns1 hi891/ hi891 fish embryos, our qRT-PCR experiments showed that the expression of glb1 was more than 2-fold enhanced, and serpine1/pai-1 expression, which can also be elevated in cellular and organismal senescence, [29][30][31] became more than 3-fold through 8-fold higher, with the advancing opaque yolk phenotype ( Fig. 6A and B).…”
Section: Concurrent Heritable Defects Of Both Spns1 and Atp6v0ca In Zmentioning
confidence: 97%
“…[25][26][27][28] First, in spns1 hi891/ hi891 fish embryos, our qRT-PCR experiments showed that the expression of glb1 was more than 2-fold enhanced, and serpine1/pai-1 expression, which can also be elevated in cellular and organismal senescence, [29][30][31] became more than 3-fold through 8-fold higher, with the advancing opaque yolk phenotype ( Fig. 6A and B).…”
Section: Concurrent Heritable Defects Of Both Spns1 and Atp6v0ca In Zmentioning
confidence: 97%
“…1 Restraint stress was induced as described previously. 3 The mice were individually housed in a room at 23Ϯ1°C on a 14/10-hour lighting schedule. Each mouse was acclimated for 1 week before initiation of restraint stress at 6 weeks.…”
Section: In Vivo Study Of Klotho Mutant Micementioning
confidence: 99%
“…Additionally, some reports have shown that SNA induced enhancement of PAI-1 mRNA, and increased PAI-1 activity. [24][25][26] More importantly, PAI-1 expression is dramatically enhanced in aged mice. In humans, elevation of PAI-1 levels occurs in several thrombotic conditions in atherosclerotic patients and aged subjects.…”
Section: Discussionmentioning
confidence: 99%